Pathways of healthcare utilisation in patients with suspected adolescent idiopathic scoliosis: a cross-sectional study. Issue 1 (June 2015) - Beauséjour, Marie; Goulet, Lise; Ehrmann Feldman, Debbie; Da Silva, Roxane; Pineault, Raynald; Rossignol, Michel; Roy-Beaudry, Marjolaine; Labelle, Hubert
Abstract Background School screening programs for adolescent idiopathic scoliosis (AIS) have been discontinued in Canada and elsewhere because they were not considered cost-effective. In communities lacking such programs, we expect a significant variety of healthcare pathways and timeframes for patient referrals to orthopaedics. The objectives of this study were: 1) to characterise the healthcare pathways of young children with suspected AIS in a population without school screening; and 2) to investigate the relationships between these healthcare pathways and the appropriateness of referrals to specialised orthopaedic clinics. Methods This study concerned all children, ages 10 to 18, referred for an initial visit for suspected AIS to any of the five out-patient paediatric orthopaedic clinics of south-western Quebec (Canada). For the 831 participants, referrals to orthopaedics were characterised as appropriate, late, or inappropriate, based on known risk factors for AIS progression and on treatment indications. Parents documented the circumstances of healthcare use prior to the orthopaedic consultation. Relevant predisposing, enabling, and need variables derived from Andersen's Behavioral Model of Health Services Use were also documented. Healthcare pathways were characterised by developing a taxonomy using multiple correspondence analysis prior to hierarchical classification. Associations between the healthcare pathways and appropriateness of referral were assessed using multinomial regression analyses. Results We constructed a taxonomy of five distinct healthcare pathways: 1) Lay/regular source of care interrelation, 2) Other professionals, 3) Lay/consultation discontinuity, 4) Other medical doctor, and 5) Regular source of care continuity. Laypersons played an important role in AIS suspicion (53 % of cases), but did not prevent late referrals. Continuity of care, as opposed to numerous uncoordinated consultations, was an effective strategy to prevent late referrals (OR = 0.32 [0.17–0.59]), but was related to increased probability of inappropriate referrals. Conclusions We identified two cardinal characteristics that distinguished the healthcare pathways and related significantly to appropriateness of referral status, namely the role of laypersons and the involvement of the regular source of care. This suggests directions for intervention such as advocating for access to a regular source of care, increasing awareness of the disease to medical practitioners' and improving their knowledge of AIS detection and referral criteria.